Modelo de competitividad del sector turístico en el Cantón Latacunga Provincia de Cotopaxi - Casamen Sandoval, Odalis Guadalupe (2022)
The present research work presents a tourism sector competitiveness model from Latacunga canton, Cotopaxi province, which combines Crouch and Ritchie's tourism competitiveness model with Porter's Diamond model. This work poses the basic question: What is the competitiveness of the Latacunga canton in relation to other cantons? The main objective is to determine the degree of competitiveness of the Latacunga canton in relation to other cantons. For the fulfillment of this objective, we began with the investigation of three antecedents of third and fourth grade degree works; in addition, of the epistemological foundation related to competitiveness models. This research is of a qualitative type oriented to the study of descriptive character; these data are of primary and secondary character. Therefore, the database of the Cotopaxi Territorial Development and Management Plan with a vision to 2025 was taken as a reference. Through this, a sample of 11 tourism agencies was used, to which an interview of 10 questions was applied, obtaining as a result that Quito is the most competitive, Latacunga is in second place, and Galapagos, due to its location, is the least competitive. As a conclusion, a model of competitiveness of the tourism sector for the canton of Latacunga was obtained, adapted to the results of the research.